2011
DOI: 10.1002/hep.24505
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of hepatitis B virus-induced immune tolerance by an immunostimulatory 3p-HBx-siRNAs in a retinoic acid inducible gene I–dependent manner

Abstract: It is extensively accepted that hepatitis B virus (HBV) escapes from innate immunity by inhibiting type I interferon (IFN) production, but efficient intervention to reverse the immune tolerance is still not achieved. Here, we report that 5 0 -end triphosphate hepatitis B virus X gene (HBx)-RNAs (3p-HBx-short interfering [si]RNAs) exerted significantly stronger inhibitory effects on HBV replication than regular HBx-siRNAs in stably HBV-expressing hepatoplastoma HepG2.2.15 cells through extremely higher expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 28 publications
6
36
0
Order By: Relevance
“…Recently, we found that an siRNA called 3p-HBx-siRNA strongly inhibited HBV replication, which was accompanied by an enhanced innate immune response against HBV. 142 Downstream of tolerance formation, breaking liver tolerance will also be required to overcome the regulatory functions of liver immune cells. This may be a difficult task for researchers to face, as the immune regulatory cells in the liver form a complex and stable network to maintain liver tolerance, as described above.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recently, we found that an siRNA called 3p-HBx-siRNA strongly inhibited HBV replication, which was accompanied by an enhanced innate immune response against HBV. 142 Downstream of tolerance formation, breaking liver tolerance will also be required to overcome the regulatory functions of liver immune cells. This may be a difficult task for researchers to face, as the immune regulatory cells in the liver form a complex and stable network to maintain liver tolerance, as described above.…”
Section: Future Directionsmentioning
confidence: 99%
“…10.1c ). While this approach was shown to promote synergistic antitumoral effects against melanoma in animal model experiments ( 8 ) or to have increased antiviral effects ( 10,11 ) , it relied on in vitro synthesized siRNAs, using bacteriophage RNA polymerase. Such enzymatic synthesis of siRNAs, although applicable for preclinical studies, presents challenges for their purity (due to the synthesis of aberrant side-products), which is a critical issue for their large-scale usage in the clinic ( 31 …”
Section: Sirnas Recruiting Tlr9mentioning
confidence: 99%
“…To address this condition, Han and colleagues (2011) designed siRNA that targeted hepatitis B virus genes, but also triggered pattern recognition receptors to engage the innate immune system. This approach significantly slowed viral replication in vivo (Han et al 2011). Therefore, RNAi can be used to either suppress or amplify immune system activation.…”
Section: Combating Infectious Diseasementioning
confidence: 99%